2012
DOI: 10.1016/j.jcin.2011.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Edge-to-Edge Mitral Valve Repair in High-Surgical-Risk Patients

Abstract: In a high-risk population, MR reduction can be achieved by percutaneous edge-to-edge valve repair, resulting in LV remodeling with improvement of functional capacity after 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 30 publications
4
43
1
Order By: Relevance
“…There was no difference in the rates of death and MR at four years follow-up, but a greater need for reoperation at one (MitraClip 20.4% vs. 2.2%, p<0.001) and four years (24.8% vs. 5.5%, p<0.001) [6]. Several series have reported outcomes in high-risk patients with MR after MitraClip, but only few with results beyond the peri-operative period [7][8][9][10][11][12][13][14][15]. A recently published systematic review has reported significantly lower observed than predicted surgical risk of mortality at 30 days (between 0% -7.8%); and lower grade of MR, NYHA class and improved quality of life after percutaneous mitral valve repair compared to pre-operative baseline [16].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…There was no difference in the rates of death and MR at four years follow-up, but a greater need for reoperation at one (MitraClip 20.4% vs. 2.2%, p<0.001) and four years (24.8% vs. 5.5%, p<0.001) [6]. Several series have reported outcomes in high-risk patients with MR after MitraClip, but only few with results beyond the peri-operative period [7][8][9][10][11][12][13][14][15]. A recently published systematic review has reported significantly lower observed than predicted surgical risk of mortality at 30 days (between 0% -7.8%); and lower grade of MR, NYHA class and improved quality of life after percutaneous mitral valve repair compared to pre-operative baseline [16].…”
Section: Resultsmentioning
confidence: 96%
“…There are few series of high-risk patients undergoing percutaneous mitral valve repair which report follow-up beyond 30 days [16]. In a recent systematic review of highrisk patients undergoing MitraClip, mortality at 30 days ranged between 0 and 7.8% [16]; survival is above 85% at six months in four reports including six-month follow-up [12][13][14][15]. The EVEREST high-risk registry comprised a cohort of high-risk patients undergoing MitraClip (STS score !12%) that was compared with a cohort of similarly high-risk patients managed conservatively [15].…”
Section: Discussionmentioning
confidence: 99%
“…In the early postoperative course, the MAE Multimorbidity, high-risk patient, contraindication for oMVS: log EuroScore > 20% and/or STS-Score >10% 11,13,14,19,21,24,26,31,35,42,43,48,49 AHA/ASC/ESC criteria for oMVS fulfilled [10][11][12]20,21,38,40,43,45,47,50 Previous cardiac surgery 13,14,20,26,40,45 Echocardiographic criteria for treatment with MitraClip system fulfilled 8,9,19,32,33 Chest radiation/porcelain aorta 8,9,16,26,45,51 Possible indications…”
Section: Recommendations For Structural Procedural and Documentatiomentioning
confidence: 99%
“…The recent introduction of MitraClip ® , the first percutaneous mitral valve repair device, provides a third therapeutic option for severe MR patients [7]. A growing body of evidence supports the increased uptake of this new therapy [8][9][10][11][12][13][14][15]. Consequently, the 2012 European Society of Cardiology guidelines suggested the use of percutaneous repair in patients with an indication for valve surgery, but judged inoperable or at unacceptably high surgical risk [16,17].…”
Section: Introductionmentioning
confidence: 99%